2014
DOI: 10.1523/jneurosci.1629-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

ATP13A2/PARK9 Regulates Secretion of Exosomes and α-Synuclein

Abstract: Kufor-Rakeb syndrome (KRS) is caused by loss-of-function mutations in ATP13A2 (PARK9) and characterized by juvenile-onset parkinsonism, pyramidal signs, and cognitive decline. Previous studies suggested that PARK9 deficiency causes lysosomal dysfunction and ␣-synuclein (␣-syn) accumulation, whereas PARK9 overexpression suppresses toxicity of ␣-syn. However, the precise mechanism of PARK9 effect on lysosomes and ␣-syn has been unknown. Here, we found that overexpressed PARK9 localized to multivesicular bodies (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
108
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(111 citation statements)
references
References 49 publications
3
108
0
Order By: Relevance
“…In terms of pathology, the proposed new pathway (Figure 1) of depolymerization of native aSyn multimers leading to the hallmark of synucleinopathies, large aSyn aggregates, will need to be further substantiated, most importantly in animal models. With cellular aSyn dyshomeostasis in PD probably being upstream of other pathological changes, the new insights reviewed here will have to be connected to other emerging themes in the field, such as the interplay between aSyn and the E3 ligase Nedd4 [69][70][71][72] and the hypothesis of cell-to-cell spreading of the protein being important in the pathogenesis of synucleinopathies [73][74][75], suggesting a potential role for aSyn release from neurons [76][77][78].…”
Section: Resultsmentioning
confidence: 99%
“…In terms of pathology, the proposed new pathway (Figure 1) of depolymerization of native aSyn multimers leading to the hallmark of synucleinopathies, large aSyn aggregates, will need to be further substantiated, most importantly in animal models. With cellular aSyn dyshomeostasis in PD probably being upstream of other pathological changes, the new insights reviewed here will have to be connected to other emerging themes in the field, such as the interplay between aSyn and the E3 ligase Nedd4 [69][70][71][72] and the hypothesis of cell-to-cell spreading of the protein being important in the pathogenesis of synucleinopathies [73][74][75], suggesting a potential role for aSyn release from neurons [76][77][78].…”
Section: Resultsmentioning
confidence: 99%
“…Through a process involving ceramide, tetraspanins, or endosomal sorting complexes required for transport (ESCRT) components, ␣-synuclein is directed into MVBs. Both PARK9 (51,52) and Rab11 (48) have been shown to promote the exosomal release of ␣-synuclein. C, APP is a cell surface transmembrane protein that can be processed by a number of proteases.…”
Section: Prion Diseasesmentioning
confidence: 99%
“…PARK9 has also been found to regulate extracellular ␣-synuclein (50). PARK9 deficiency causes lysosomal dysfunction and ␣-synuclein accumulation, whereas PARK9 overexpression suppresses cellular toxicity of ␣-synuclein (51,52). Importantly, PARK9 is also involved in the biogenesis of exosomes and has been found to increase exosomal ␣-synuclein (51, 52).…”
Section: Mechanisms and Physiological Conditions For The Release Of ␣mentioning
confidence: 99%
“…On the other hand, αSYN oligomers in the lysosome may impact on GBA, leading to its malfunction and creating a vicious cycle of lysosomal failure and pathological αSYN accumulation (Mazzulli et al 2011). Another piece of evidence showed that mutations in the ATP13A2 gene, which encodes a lysosomal ATPase cation transporter and causes autosomal recessive familial PD (PARK9, also known as Kufor-Rakeb syndrome), enhances αSYN aggregation and affects its exosomal secretion into the extracellular space (Tsunemi et al 2014;Lopes da Fonseca et al 2016). Taken together, these genetic discoveries strongly support the notion that the defects in endo-lysosomal trafficking/functions are illuminated as convergent mechanisms for PD and related neurological disorders.…”
Section: Membrane Trafficking Defect In Parkinson's Diseasementioning
confidence: 99%